A note on the weighted log canonical threshold - Nguyen Van Phu (Comptes Rendus. Mathématique)
In this paper, we introduce and study a set relative to singularities of plurisubharmonic functions. We prove that this set is countable under the condition $h>0$ on $\mathbb{B}\setminus \lbrace 0\rbrace .$